Пошаговое объяснение:
в этом примере не надо брать производную от дроби
постоянный множитель (2/3) можно вынести за знак производной
y'=((2/3)x³)'= (2/3)(x³)'=(2/3)3x²=2x²
(k*aⁿ)'=k*n*aⁿ⁻¹
(2/3 * x³)' k=2/3; n=3 тогда
(2/3 * x³)'=2/3 * 3 * x³⁻¹=2x² - это ответ.
Пошаговое объяснение:
в этом примере не надо брать производную от дроби
постоянный множитель (2/3) можно вынести за знак производной
y'=((2/3)x³)'= (2/3)(x³)'=(2/3)3x²=2x²
(k*aⁿ)'=k*n*aⁿ⁻¹
(2/3 * x³)' k=2/3; n=3 тогда
(2/3 * x³)'=2/3 * 3 * x³⁻¹=2x² - это ответ.